Utilization of correlation and cointegration relationships in quantitative trading - Strnad, Vladimír; Fičura, Milan; Málek, Jiří, 1953-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2016)
This thesis gives an overview of measure of dependence used in Finance with the motivation of showing the shortcomings and advantages of different metrics and stress how crucial it is to capture the dependence properly given its use in constructing investment portfolios and risk management.In second part of the thesis we introduce the notion of cointegration, explain its implication and how it is being used in context of statistical arbitrage trading strategy. We then utilize cointegration relationship in constructing such strategy and testing its effectiveness in three different sectors of the stock market and showing the advantage of such strategy.
Vedoucí práce: Milan Fičura
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses